Planning, coordination and control of multi-fingered robot hands - Chen, Jun. (2010)
In this thesis, the problem of controlling multi-fingered robot hands is addressed. Several issues are explored in this research. These issues involve the kinematic analysis and modeling, dynamic analysis and control, contact force analysis and optimization, planning of the coordination of the hand-object system, and adaptive impedance control of multi-fingered robot hands.